Unpacking the sociotechnical challenges of IoT design work in practice - Castle-Green, Teresa (2023)
The term `Internet of Things' (IoT), was coined in 1999 (Ashton et al., 2009), and has continued to grow under this heading since its conception with a number of subheadings developed (such as, the Industrial Internet of Things (IIoT)) to give further classification as the field has expanded. By 2014 the IoT was being considered as an industry in its own right, "with the potential to have a greater impact on society than the  rst digital revolution" (Walport, 2014, p. 6). The Internet of Things is a growing industry spanning many different markets and sectors with worldwide device forecasts going from 9.7 billion in 2020 to over 29 billion in 2030 (Vailshery, 2022).